Karya Tari Titik Temu Temu Interpretasi Bentuk Kajanglako Dalam Prosesi Alek Bajawek Kabupaten Dharmasraya - Alif, Suci Nur; Stevenson, Yan; Syahril Syahril; Wahida Wahyuni (JURNAL ILMIAH NUSANTARA, 2025)
The Titik Temu dance piece was inspired by a building found in a cultural procession, the Alekbajawek. Within this procession, a structure, called a kajanglako, is constructed for the needs of the Alek. The artist's work focuses on the meaning of the Kajanglako structure, namely the old pillar and the long batik cloth, which represent the important roles of men and women in this procession, without which the procession would be impossible. Awareness of the importance of these roles is discussed in the Titik Temu dance piece. This work utilizes Alma M. Hawkins' dance creation approach in her book Creating Through Dance and Choreography: Form, Technique, and Content. This approach consists of stages: data collection and field observation, exploration, improvisation, formation, and evaluation. The work is also enhanced by the use of lighting to depict the atmosphere and conflict in finding decisions when establishing the Kajanglako. The Titah Titik Temu dance piece utilizes an abstract style and is performed on the proscenium stage of the Hurijah Adam performance building.